The Phenomenon of the difficulties of the Students’ in translating unfamiliar Words by Using Context Clues Techniques - Nur Islah Amaliah; Muhammad Zuhri DJ (ELTIES : English Language Teaching for EFL Learners, 2023)
The purpose of this study was to comprehend the phenomenon of student difficulties and the students' responses to the use of the context clues technique, particularly in translating unfamiliar words. The data were collected in the eighth grade. In five meetings, the writers taught the context clue technique to twenty-three students. The student’s difficulties were observed by the observation checklist during the teaching and learning process. The students’ responses were collected by the interview section in the last meeting. The results of the data analysis showed that the students had several difficulties, such as difficulty understanding context clues, difficulty translating the meaning of words due to a lack of vocabulary mastery, and difficulty guessing word classes. The results of the students’ responses were positive. It was demonstrated by their enthusiasm for the teaching and learning processes. They also suggested using the context clues technique in class.